Valorization of pinecone as a pyrolysis feedstock: identification of bio-oil and synthesis of activated biochar for Cr(VI) elimination from wastewater - Alfares, Amenah Adnan; Younis, Afyaa Muayed; Rasheed, Lana Abdalhameed; Fadhil, Abdelrahman Basil (Comptes Rendus. Chimie)
The thermal pyrolysis of pinecone (PC) to produce pyrolytic oil (PO) and solid biochar (BC) in a batch-scale fixed-bed reactor at numerous temperatures (400–600 °C) for diverse time intervals (30–120 min) using different particle sizes (0.26–0.841 mm) and various rates of heating (10–50 °C/min), as established in this work, led to the production of a high yield of the PO (42.12%) at 500 °C for 1 h with a 0.40 mm particle size and a heating rate of 30 °C/min. The bio-oil (BO) content in the resulting PO amounted to 10.20%. The 1H NMR and GC-MS spectroscopy, besides the ultimate analysis of the BO, were identified. The consequences disclosed that the BO principally consisted of oxygenated hydrocarbons, which amounted to 54.98%, besides the N-organic compounds and hydrocarbons, whose contents were 6.95% and 2.60%, respectively. The BO had a high content of C and H besides its remarkably high caloric value (26.99 MJ/kg), suggesting its potential as a high-energy fuel. The K2CO3-activation of the BC leftover after the pyrolysis of PC produced a microporous activated biochar (ABC) with a BET surface area of 465.55 m2/g and 1.97 nm average pore diameter using 2:1 K2CO3:BC impregnation ratio at 750 °C for 1 h. The ABC exhibited an adsorptive elimination of 98.71% for 100 mL of solution containing 150 ppm of Cr(VI) from its aqueous phase using 0.20 g of ABC at 35 °C for 140 min and a pH = 2.0. The Langmuir isotherm and the psedue-2nd-order model of kinetics best described the Cr(VI) adsorption by the ABC. In conclusion, PC could be used as a pyrolysis feedstock to produce BO with high-content aromatic oxygenates besides ABC with a high surface area, a microporous structure and an efficient ability to eliminate Cr(VI) ions from wastewater.